Responsibility of The Expedition Company to Sea Freight Service Users Who Experience Loss and Damage to Goods in The Port Area - Siahaan, Richa Yohana Rusli; Anggusti, Martono; Haryono, Fadillah (Golden Ratio of Data in Summary, 2025)
Sea transportation is an important component in international trade, which plays an important role in the distribution of goods. However, there are losses greater than the losses caused by the transportation itself, such as shortages, damages, and loss of goods, which can arise during the process of unloading at the port carried out by the freight forwarding company by sea. This study aims to examine the limitation of responsibility in the legal relationship between freight forwarding companies, carriers, and sea transportation expedition companies in the context of sea transportation activities. Using a normative legal research methodology, this research relies on sources of legal materials, including laws and regulations and court decisions/rulings, using a legislative approach and a case approach. The results of this study show that, first, the limitations on the responsibility of the expedition party are regulated in Article 87 of the Commercial Code, as well as the limitations on the responsibility of the carrier regulated in Article 40 and Article 41 of Law Number 17 of 2008, and the responsibility of the sea freight expedition company in terms of providing facilities, licensing, supervision, and the implementation of order of sea transportation activities, as stipulated in Cassation Decision Number 2665 K/Pdt/2022 which corroborates the decision of the first judge in case Number 728/Pdt.G.2016/PN.Mdn, has been appropriate and fulfills the legal objectives that provide certainty, justice, and usefulness.